Human and Bear Post - Adelaide de Menil (1967)
Human figure wearing the double blackfish hat. This carving recounts the acquisition of a helmet from the Tsimshains at the Battle of the Stikine. The other pole is the Supernatural Grizzly Bear pole, or the Bear up the Mountain pole.